The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/fst.96621
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of japonica sorghum following microwave intermittent drying based on label-free technology

Abstract: The aim of this study was to investigate the influence of microwave drying on the protein quality of japonica sorghum following an intermittent drying test. Using label-free technology and liquid chromatography-tandem mass spectrometry for proteomic analysis, the effects of microwave drying on sorghum differential protein expression, functional classification, and metabolic pathways were analyzed at the molecular level. After sorghum was dried using a microwave, 85 differential proteins were identified. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…The maritime pine (Pinus pinaster) and eucalyptus (Eucalyptus globulus) are two Portuguese wood species widely used for furniture, fences, and structural purposes. Analyzing small cores of wood treated in the MW, observed that eucalyptus heartwood takes longer to dry compared to pine heartwood, and the absorption of water after using MW obtained better impregnability than the control heartwood, being a viable possibility in the wood industry to work the raw material [15][16][17][18]. This example, and others related to the humidity of woods, shows all the versatile proposes the MW drying could have.…”
Section: Introductionmentioning
confidence: 79%
“…The maritime pine (Pinus pinaster) and eucalyptus (Eucalyptus globulus) are two Portuguese wood species widely used for furniture, fences, and structural purposes. Analyzing small cores of wood treated in the MW, observed that eucalyptus heartwood takes longer to dry compared to pine heartwood, and the absorption of water after using MW obtained better impregnability than the control heartwood, being a viable possibility in the wood industry to work the raw material [15][16][17][18]. This example, and others related to the humidity of woods, shows all the versatile proposes the MW drying could have.…”
Section: Introductionmentioning
confidence: 79%
“…Therefore, it is necessary to study the mechanism of crack formation in corn kernels based on their temperature and water content. At present, the research on microwave drying mainly focuses on obtaining the best process parameters for drying different materials, as well as studying the germination rate, ketone content, protein content, amylose content, and other characteristic parameters of materials after drying (Çelen, 2019; Chahbani et al, 2018; Lv et al, 2018; Zhang et al, 2022). De Faria et al (2020), and Song et al (2013) studied the power, time, temperature, and moisture content during the microwave drying process of corn, which played a certain role in the study of corn microwave drying technology but ignored the influence of temperature and moisture content on drying cracks.…”
Section: Introductionmentioning
confidence: 99%